INDICATORS OF SCIENCE, TECHNOLOGY AND INNOVATION FORTHE COMPETITIVE INTELUGENCE OF REGIONAL INNOVATION SYSTEMS - Cancino Salas, Ronald; Petit-Breuilh, Jorge; Padilla, Patrício; Mendoza, Yenniel; García, Mauricio; Gatica, Mario; Mellado, Felipe (Cuadernos de Administración, 2008)
The article proposes that he current process of deepening the Nationai System of Innoation in Chile, it is necessary to build and enhance regional innovation systems Iike strateg. for incorporating the local ization processes of the innovation in the way that cou[d be possible to articulate nationa[ priorities ( Se[ective clustering) with the emerging innovation processes from the territory enhanced from sub-national level (regions). In this context, we propose a model for regional innovation management and its examines the methodology of Regional Competitive Intelligence in its magnitude ofregional ana[ysis of the capabilities and potentia[ of STI. Its proposes a strategy, a set articulated of techniques and indicators for related Advanced Capital Human, build of techno economics networks and techno scientifics, indicators of focus of STI, of priorities of public investment and of economic dynamics of sectoral / regional. These indicators are built with the horizon to initiate processes of modeling and simulation of Regional Innovation System in technoJogy foresight processes.